2021
DOI: 10.3389/fpsyt.2021.731378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Working After Retirement on the Mental Health of Older People: Evidence From China

Abstract: There is little empirical research on the effect of working after retirement on the mental health of the older adults in China. To fill this gap in the literature, this study examines the effects of working after retirement on the mental health of the older adults using data from the China Family Panel Studies. We employed the methods of ordinary least squares, ordered logit, and propensity score matching–difference in differences (PSM–DID). Results show that working after retirement is negatively related to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Table 5 shows the 15 articles [ 67 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ] included in the reviewed studies on the topic of sociodemographic characteristics of older adults and their perceived well-being in green spaces. From a demographic perspective, the differential impact of the perception of green space on health and well-being is an important element of previous studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 5 shows the 15 articles [ 67 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ] included in the reviewed studies on the topic of sociodemographic characteristics of older adults and their perceived well-being in green spaces. From a demographic perspective, the differential impact of the perception of green space on health and well-being is an important element of previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…Following the literature review, we also found several studies stating that older people who choose to continue working even after retirement because of the possibility of gaining social participation and social support contribute to their meaning and purpose in life. This would help to improve their mental health and well-being and reduce their mortality rates [101]. None of the 65 articles included in the review have been analyzed for knowledge topics with the help of visualization software.…”
Section: Influence Of Sociodemographic Characteristics On Older Peopl...mentioning
confidence: 99%
“…Lee and Smith (2009) found that Korean retirees showed more depression than workers. Among Chinese older adults, working after retirement was found to be negatively associated with mental health (Xie et al ., 2021). In the current study, we will control individuals' demographic and socioeconomic characteristics and perform a subgroup analysis for retired and non-retired elderly.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The change in social roles and lifestyles due to retirement can easily lead to depression and other mental health problems among the elderly [8]. Therefore, employment is regarded as an essential factor affecting the mental health of older people [9].…”
Section: Introductionmentioning
confidence: 99%